Intravascular Histiocytosis Associated with Bacterial Endocarditis - Linkeviciute, G.; Petkevicius, A.; Makstiene, J.; Gudinaviciene, I.; Valiukeviciene, S.; Mahrle, G. (Aktuelle Dermatologie, 2014)
A 63-year-old woman presented with a 6-month history of malaise, fever, weight loss and violaceous indurated skin patches on her earlobes, elbows, knees, and upper arms. Based on clinical findings and positive Borrelia burgdorferi IgG antibodies, a diagnosis of an inflammatory-edematous stage of Acrodermatitis chronica atrophicans could not be excluded. After treatment with Cephalosporin for 3 weeks skin lesions reduced. However, malaise, fever, anemia, leukopenia, thrombocytopenia, and elevated amounts of CRP, ESR, liver enzymes remained. Skin histology and immunohistochemistry revealed vascular proliferation with intravascular cells positive for LCA and marker of histiocytes CD68. According to clinical and immunohistochemical findings intravascular histiocytosis associated with infectious endocarditis was diagnosed. Transoesophageal heart sonography supported a diagnosis of infectious endocarditis. The patient was treated with Benzylpenicillin intravenously for 21 days. Heart valve replacement surgery was performed.Intravascular histiocytosis (IVH) is a rare reactive cutaneous lesion of unknown pathogenesis. A diagnosis of it may necessitate further clinical evaluation to exclude the possibility of co-existent systemic disease.